Proposta metodológica para subsidiar a determinação do grau de impacto ambiental em empreendimentos minerários na região de Descalvado e Analândia - Torresan, Fábio Enrique (Universidade Federal de São Carlos, 2005)
This paper has the main objective of proposing methodological procedures for the analysis of the environmental impact degree and respective compensation calculation, in accordance with the Article 36 of Law 9.985. The research was consolidated through a case study specifically applied for the analysis of mining enterprises, in the region of Descalvado an Analandia, Sao Paulo State, Brazil. Through the application of geoprocessing tools, environmental information were converted into environmental impact degree indicators, related mainlyto the intensification of erosive processes, biodiversity loss and impacts on the hydrological resources. The present methodological proposal represents an important instrument of environmental management for the assessment of conservation priorities and alternatives for location of enterprises. The results showed that the region of Descalvado and Analandia presents high environmental fragility, due to it's high potencial to cause erosion and also due to their fragments of natural vegetation. It was proposed the creation of an Protected Area.
Keywords: Impacto ambiental - avaliação; Geoprocessamento; Minas e recursos minerais; Ecologia da paisagem; Environmental impact assessment; Environmental compensation; Mining; Protected area; Geographic information system; Landscape ecology; Erosion; CIENCIAS BIOLOGICAS::ECOLOGIA